2004
DOI: 10.1111/j.1469-8137.2004.01284.x
|View full text |Cite
|
Sign up to set email alerts
|

Russulaceae and Thelephoraceae form ectomycorrhizas with members of the Nyctaginaceae (Caryophyllales) in the tropical mountain rain forest of southern Ecuador

Abstract: Summary• Three members of the Nyctaginaceae, two Neea species and one Guapira species, occurred scattered within a very species-rich neotropical mountain rain forest. The three species were found to form ectomycorrhizas of very distinctive characters, while all other tree species examined formed arbuscular mycorrhizas.• The ectomycorrhizas were structurally typified according to light and transmission electron microscope investigations. The internal transcribed spacer (ITS) rDNA and part of the nuclear large s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 44 publications
2
45
1
5
Order By: Relevance
“…Thus, this study lends no support to the hypothesis of general mycobiont specificity in the plant family Nyctaginaceae (Chambers et al, 2005;Haug et al, 2005;Suvi et al, 2010). Re-analysis of the EcM fungal community of shrub 'C' of Neea sp1 (sensu Haug et al, 2005) in an Andean cloud forest revealed a species of Clavulina in addition to members of the Russulaceae and Thelephoraceae reported previously. In Yasuni, four out of six most frequent EcM fungal species displayed host preference.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Thus, this study lends no support to the hypothesis of general mycobiont specificity in the plant family Nyctaginaceae (Chambers et al, 2005;Haug et al, 2005;Suvi et al, 2010). Re-analysis of the EcM fungal community of shrub 'C' of Neea sp1 (sensu Haug et al, 2005) in an Andean cloud forest revealed a species of Clavulina in addition to members of the Russulaceae and Thelephoraceae reported previously. In Yasuni, four out of six most frequent EcM fungal species displayed host preference.…”
Section: Discussioncontrasting
confidence: 44%
“…In South America, this information relies on fruit-body observations (Pegler, 1983;Singer et al, 1983;Henkel et al, 2002;Laessøe and Petersen, 2008) and limited root sampling of Nyctaginaceae (Haug et al, 2005) and Dipterocarpaceae (Moyersoen, 2006). Here we tested the hypothesis that particularly Nyctaginaceae hosts associate with a few EcM fungi that belong exclusively to the Thelephoraceae and Russulaceae families (Chambers et al, 2005;Haug et al, 2005). Based on the general latitudinal biodiversity gradient (Hillebrand, 2004) and the anticipated correlation between EcM fungal and host plant diversity (Dickie, 2007), we hypothesized that EcM fungi are highly diverse in a primary neotropical forest site.…”
Section: Introductionmentioning
confidence: 99%
“…see Tometella sublilacina clustering with species in Thelephora). Similar findings have been reported in several recent studies on Tomentella/Thelephora using ITS sequences (Haug et al, 2005;Taylor & McCormick, 2008). More detailed taxonomic investigations of their microscopic and macroscopic features coupled with the analyses of multiple additional genes from more species are needed to resolve these taxonomic issues.…”
Section: T Sha and Otherssupporting
confidence: 54%
“…where patterns of host specificity were reported (Bechem & Alexander, 2011;Haug et al, 2005;Tedersoo et al, 2010a), recent tropical EcM biodiversity surveys have shown that co-occurring (sympatric) tree species including different tree families can be colonized by identical dominant EcM fungi (Diédhiou et al, 2010;Smith et al, 2011;Tedersoo et al, 2011). These sympatric tree families included the Dipterocarpaceae and Caesalpiniaceae in the Paleotropics (Tedersoo et al, 2007(Tedersoo et al, , 2011.…”
Section: Ecm Fungal Communities Comparison Between P Dipterocarpaceamentioning
confidence: 92%
“…Recent studies indicate that trends in EcM fungal biodiversity are not simply driven by a latitudinal gradient . Biodiversity depends on the forest type under study (Brearly, 2011;Smith et al, 2011) and is also influenced by host identity (Haug et al, 2005;Tedersoo et al, 2010a). Amongst the EcM surveys in Dipterocarpaceae vegetation (see Brearly, 2011 review and references therein), comparisons could be made with a SE Asian Mixed-dipterocarp forest (Peay et al, 2010), where diversity was measured in plot size identical to this study.…”
Section: Ecm Community Diversity and Structure In P Dipterocarpacea mentioning
confidence: 97%